(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: This study examines how return on assets (ROA) and the debt-to-equity ratio (DER) influence firm value, measured by price-to-book value (PBV), in Indonesia’s transportation and logistics sector, and assesses the moderating role of DER in the ROA-PBV relationship. It also interprets the findings through the economic dimension of the Asta Gatra framework to explain their relevance to economic resilience and national growth. Study Design/Methodology/Approach: This study applies a quantitative approach using secondary panel data from transportation and logistics companies listed on the Indonesia Stock Exchange. Purposive sampling selected 27 companies from a population of 37 companies for the 2021-2024 period. The study analyses the data using panel-data regression and tests DER as a moderating variable. Findings: ROA and DER positively and significantly affect PBV. The interaction between ROA and DER also has a positive and significant effect on PBV, indicating that DER strengthens the relationship between profitability and firm value. These findings show that effective asset utilisation and capital structure management strengthen firm value and support the financial resilience of transportation and logistics companies, with broader implications for economic resilience. Originality/Value: This study extends firm-value research by examining DER as a moderator of the ROA-PBV relationship in Indonesia’s transportation and logistics sector. It also integrates an Asta Gatra perspective to connect firm-level financial performance with the broader discussion of economic resilience and national growth.